Strategy Development Tourism Destination in Kampung Adat Praiijing, West Sumba - Dewi, Liliana; Septiana , Merry (CV ODIS, 2023)
This study aims to determine the strategy development of tourism destinations in Kampung adat Paiijing, West Sumba. Qualitative and quantitative method is used in this research. The respondent is the Head of Desa Tebara, West Sumba, communities, and visitors of Kampung adat praiijing. The result showed that attraction, amenities, and accessibility (3A) play an essential role in developing tourism destinations in Kampung adat Praiijing. Meanwhile, the SWOT analysis result identified that the 3A are parts of creating villages by maintaining and preserving the beauty of natural resources and cultural interest, improving supporting facilities, and providing training to the community concerning tourism program